Customer delight and work engagement. Issue 5 (5th August 2014) - C. Barnes, Donald; E. Collier, Joel; Robinson, Stacey
Abstract : Purpose: – The purpose of the current research is to evaluate how customer contact level and customer service-based role conflict influence the relationship between customer emotions and work engagement, while simultaneously evaluating psychological capital as an outcome of work engagement. Customer service research highlights the impact of employee attitudes and behaviors on customer satisfaction. More recently, this relationship has been examined in reverse, evaluating how customer emotions influence the employee. Unfortunately, previous research has not evaluated variables that inhibit the impact of customer emotions on the employee. Design/methodology/approach: – Data were collected from frontline employees across high and low customer contact service contexts. The hypothesized relationships were tested using structural equation modeling. Findings: – This research provides empirical evidence that employee-perceived customer delight impacts employee work engagement. However, through a process of feedback, customer service-based role conflict impacts the relationship between customer emotions and employee emotions. Finally, the conceptual model illustrates how engaged employees can create their own personal resources vis-à-vis the broaden-and-build theory of positive emotions. Research limitations/implications: – This research identifies both antecedent and outcomes variables associated with work engagement, as well as identified mediating factors. Practical implications: – Results suggest that the quality and level of contact that frontline employees have with customers impact their work engagement. Furthermore, engaged frontline employees have the ability to create their own personal resources. Originality/value: – This research makes contributions to the understanding of the impact of positive customer emotions on frontline employees.